ERGONOMIC PRODUCT CREATION: A STRATEGIC CONCEPT OF COMPETITIVE ADVANTAGE - Nugraha Saefudin (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
The creation of the best and different values for consumers will make business people continue to exist, so this value must be owned for competitive advantage. One of the value creation is ergonomic product design. This article focuses on the ergonomic design of classrooms for educational service providers. Environmental problems in the classroom: school physical environment, safety, safe, comfortable and healthy classrooms need to be complemented by an ergonomic product value approach to maximize product benefits. Ergonomic classroom design is the creation of product value for educational service organizations, where the classroom is a place of interaction between producers and consumers. The ergonomic design of classroom space, an s umber power key to customer satisfaction towards the successful organization of educational services, competitive advantage is based resource (Resource-based View - RBV)